Model Kompetensi Kewirausahaan untuk UMKM di Kota Pontianak dalam Menghadapi Persaingan Global - Rizki Fakhrul Yahya; Wilda Sari (Yayasan Literasi Sains Indonesia, 2026)
This study aims to examine the effect of entrepreneurial competencies on the competitiveness of culinary micro, small, and medium-sized enterprises (MSMEs) in Pontianak City. Entrepreneurial competencies are operationalized through innovation and technology competence, managerial and social competence, and the external environment as a contextual factor. A quantitative approach was employed using a survey method involving 200 culinary MSME owners selected through purposive sampling. Data were collected using structured questionnaires and analyzed using multiple linear regression with SPSS. The results indicate that all measurement instruments are valid and reliable, and the regression model satisfies classical assumption tests. Partially, innovation and technology competence has a positive and significant effect on MSME competitiveness (β = 0.361; p < 0.05), managerial and social competence also shows a positive and significant effect (β = 0.168; p < 0.05), and the external environment exerts a positive and significant influence (β = 0.356; p < 0.05). Simultaneously, these variables significantly affect MSME competitiveness, with an adjusted R² value of 0.915, indicating that 91.5% of the variance in competitiveness is explained by the proposed model. These findings confirm that MSME competitiveness is not solely determined by external market conditions but is strongly driven by internal entrepreneurial competencies supported by a conducive business environment. This study provides practical implications for policymakers and stakeholders in designing integrated MSME development programs that emphasize strengthening innovation and technology capabilities, managerial and social competencies, and supportive entrepreneurial ecosystems to enhance competitiveness and sustainability.